Study on the Conversion of Conventional Cooperatives to Sharia System - Maulida, Dian; Elvira, Rini (Darul Yasin Al Sys, 2025)
The objective of the present study is to examine and ascertain the obstacles encountered in converting Assa'Adah Multipurpose Cooperative (KSU) into a Sharia cooperative. The present study utilizes field research with descriptive qualitative methods, incorporating data collection techniques such as observation, structured interviews, and literature studies. The study's findings reveal that the primary obstacles at this stage stem from members' lack of understanding of what a Sharia cooperative is, leading to divergent views on the matter, with some members expressing positive sentiments and others negative. The transition process is encountering impediments in transferring member credit into financing without usury, necessitating the attendance and signature of all members on a letter of agreement if they wish for their credit to be transferred into the form of Qard. The PAD encountered impediments when a notary approved the PAD draft, a process that previously required the signature of the Sharia Supervisory Board. The absence of a DPS with a certificate of education and training from DSN-MUI further complicates the situation. Two key factors hinder the implementation of Sharia principles in cooperative enterprises. Firstly, there is a dearth of knowledge regarding sharia principles among the management and members of these cooperatives. Secondly, the prevalence of conventional operational practices impeded the application of sharia principles in cooperatives. The conversion of business activities is further hindered by the absence of contracts that are by Islamic principles. The possibility of reverting to a conventional cooperative model is not impeded. The Assa'Adah cooperative, in its comprehensive nature, is dedicated to the ongoing conversion process and the strict adherence to Sharia principles despite the protracted nature of this undertaking.